Enhancing quality of life: the impact of public parks and open space on the public perception in Sungai Petani, Kedah / Zikril Ikhwan Zakrullah and Zulkefle Ayob - Zakrullah, Zikril Ikhwan; Ayob, Zulkefle (2024)
This study aims to determine the connection between public open spaces (POS) and quality of life (QOL) in Sungai Petani, Malaysia, among other urban environment issues in a growing country that affect the decline of POS quality and quantity. The challenges and context of the study include the growing urbanisation of metropolitan areas, which has sped up city growth and created a need for more green spaces. The study aims to determine how public parks and open spaces affect urban residents' quality of life by looking at aspects of their physical and mental health, social interactions, and sense of community while also identifying design elements and management strategies that increase the effectiveness of public parks and open spaces in enhancing QOL and fostering sustainable development. The degree of satisfaction with the POS and QOL components was used to obtain community perception using the 1–5 Likert scale. According to the study, the 'function' aspect has the most impact on how consumers perceive POS. The most important aspect influencing people's physical QOL is ‘health’. Finding shows a considerable link between POS and physical QOL.